CHARACTER VALUES ADDRESSED IN STUDENT’S ENGLISH TEXTBOOK OF EIGHT GRADE BASED ON K 13 CURRICULUM - Widia Septrisna; Eliza Eliza; Widya Syafitri (Universitas Mahaputra Muhammad Yamin, 2019)
This article is written based on a research that has been conducted. This research aimed to analyze the character values ​​found in the textbook used in the 8th grade of the Junior high School